Соотношение полов и смертность Anastatus japonicus (Hymenoptera, Eupelmidae) в зависимости от численности хозяина - Зелинская, Л.М. (Вестник зоологии, 1981)
A three-year study of the Anastatus disparis amount dynamics in different stands of the Lower Dnieper area made it possible to establish that in the Porthetria dispar L. centres, characterized by growth, peak or depression of the amount, females dominate in the Anastatus populations (54-68% on the average); at the crisis phase the female number lowers down to 27%. An increased death rate of Anastatus in the host egg shells (above 20%) was observed in the P. dispar L. populations with intensive microsporidia invasion (the crisis phase).